Cohesion and Coherence of Discourse in the Story of "Layangan Putus" on Social Media Facebook - Latifah, Ani; Triyono, Sulis (Indonesian Journal of EFL and Linguistics, 2020)
This research is to find out how the use of cohesion and coherence in the story of "Layangan Putus", which was viral some time ago. Cohesion and coherence are important criteria and principles in a text. This research is expected to contribute to the development of the quality of story writing. So the story can be understood and useful for the readers. Thus, the purpose of writing stories can inspire readers. The method used to analyze cohesion and coherence was a descriptive analysis seen in each paragraph. The cohesion aspects analyzed were lexical and grammatical cohesion aspects. The results of this study indicated that the story of "Layangan Putus" had aspects of lexical cohesion, grammatical cohesion, and coherence. Aspects of cohesion and constructive coherence in which discourse can convey a message to readers. In this way, the contents of the story can make the reader into feeling what the writer feel.